Synthesis and characterisation of jatropha oil-based waterborne polyurethane dispersions - Saalah, Sariah (2016)
The transition from solvent-borne to waterborne polyurethane (PU) coatings is driven by the stringent regulations to reduce emissions of volatile organic compounds (VOCs) from the products, enhanced by the increasing awareness of the consumers of safety and health issues. On the other hand, a low cost, abundant, and renewable vegetable oil source is now receiving increasing attention for polyurethane production.Previous studies reported the possibility of the production of PU coatings, adhesives and elastomers from non-edible jatropha oil. However, as far as is known, no study has reported on waterborne PU synthesis from jatropha oil. In this research, jatropha oil is modified to polyol to be used as a starting material for the production of a waterborne PU dispersion. A series of jatropha oil-based polyols (JOLs) were synthesised from jatropha oil by a two-step process, namely epoxidation and oxirane ring opening. The effect of epoxidation conditions on the properties of the JOLs was investigated. The JOLs are liquid under room conditions with a hydroxyl number in a range of 138 to 217 mg KOH/g.The jatropha oil-based waterborne polyurethane (JPU) dispersions were produced by polymerising the JOLs with isophrene diisocyanate (IPDI) and dimethylol propionic acid (DMPA). The colloidal stability of the resulting JPU dispersions were studied by particle size analysis and rheology measurements. Inclusion of up to 5.4 wt.% of DMPA as an internal emulsifier produced a wide range of particle sizes from 84 nm to 825 nm. However, further increasing the DMPA content up to 6.8 wt.% resulted in smaller particles but a multimodal particle size distribution was obtained for the dispersion synthesised from low OH number polyol. The dispersions have a solid content of 22.9 to 26.9 wt.% with a relatively low viscosity in the range 5.6-53.1 mPa.s. The JPU dispersions exhibited the typical flow behaviour of the commercial polyurethane dispersions, ranging from almost Newtonian to a shear thinning fluid, and the experimental data correlated well with the Cross model. The samples were stable after 18 months of storage under room conditions.A films with up to 62 wt.% bio-based content were successfully produced after evaporation of water from the JPU dispersion. The chemical, physical, mechanical and thermal properties of the films were characterised. The experimental data revealed that the OH number of the JOLs, DMPA content and the hard segments were the key parameters which control the structure and the properties of the JPU films. The JPU film derived high OH number polyol and high hard segment content exhibited the highest crosslinking density. This contributed to higher hardness, better mechanical properties, and hydrophobic surface character. The films show an elastomeric polymer behaviour and good thermal stability.The JPU dispersions were applied on a wood surface and the performance of the coatings were evaluated. The JPU films have excellent adhesion to the substrate, excellent optical properties as well as chemical and abrasion resistance. The PU dispersions synthesised in this work possess good properties with a promising application as a standalone coating or binder for wood and decorative coatings.